2018
DOI: 10.1002/aocs.12035
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structural Analysis of Fat Crystal Networks by Means of Raman Confocal Imaging

Abstract: The techniques that are currently available to assess fat crystal networks are compromised with respect to invasive sample preparation and ability to quantify compositional and structural features. Raman confocal hyperspectral imaging coupled to analysis with multivariate curve resolution can address these bottlenecks, as it provides label‐free, noninvasive chemical information in three dimensions (3D). We demonstrate the ability to acquire compositional maps of dispersions of micronized fat crystals (MFC) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…This observation is in accordance with the weak‐link network of fractal fat crystal networks as shown by Martens et al. [ 32 ] and Nikolaeva et al. [ 32,33 ] Indeed, De Graef [ 34 ] observed a comparable morphological evolution during static crystallization and subsequent isothermal crystallization for palm oil.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This observation is in accordance with the weak‐link network of fractal fat crystal networks as shown by Martens et al. [ 32 ] and Nikolaeva et al. [ 32,33 ] Indeed, De Graef [ 34 ] observed a comparable morphological evolution during static crystallization and subsequent isothermal crystallization for palm oil.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, Martens et al. [ 32 ] recently showed evidence of the presence of a crystalline phase in the oily inter‐spherulite space using Raman Confocal Imaging spectroscopy. Moreover, they showed that the spherical dense aggregates were in fact highly porous.…”
Section: Resultsmentioning
confidence: 99%
“…Full details of the experimental procedures can be found elsewhere. 33,34 In short, experiments were performed on a WITec confocal Raman (Alpha 300R+) microscope equipped with a Zeiss upright microscope with a 532 nm laser at 25.0 mW. The sample was placed on a 19°C water-cooled plate.…”
Section: Raman Imagingmentioning
confidence: 99%
“…Fractal dimensions D were determined by the box-counting method, which assessed fractality with better precision compared to other approaches. 33 An image is overlaid with boxes of decreasing size, determining for each box size how many boxes contain ( part of ) a self-similar object. The relationship between the number of filled boxes (N b ) and the length of the boxes (l b ) provides the fractal dimension D:…”
Section: Raman Imagingmentioning
confidence: 99%
See 1 more Smart Citation